2008
DOI: 10.1007/s11182-008-9095-1
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the protective properties of cermets of combined structure under high-velocity impact

Abstract: The use of self-propagating high-temperature synthesis (SHS) for the production of cermets of combined structure is considered and a mathematical simulation of the behavior of these materials under high-velocity impact by a projectile is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…To investigate the behavior of materials under shock-wave loads, a mathematical model is suggested that allows the stress-deformed state and fracture of plastic and fragile materials to be calculated under shock-wave loads in the context of mechanics of continuous media [6,7,[9][10][11]. The dynamic fracture is considered as a process of growth and merging of microdefects due to stresses formed under loading.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the behavior of materials under shock-wave loads, a mathematical model is suggested that allows the stress-deformed state and fracture of plastic and fragile materials to be calculated under shock-wave loads in the context of mechanics of continuous media [6,7,[9][10][11]. The dynamic fracture is considered as a process of growth and merging of microdefects due to stresses formed under loading.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest are investigations into the deformation and fracture processes developing in ultrafine-grained and nanostructured materials under pulsed and shock loading [1][2][3][4]. These investigations provide information on the fundamental strength properties of the materials.…”
mentioning
confidence: 99%